Analisis Kinerja Sumber Daya Manusia Dengan Pendekatan Human Resources Score Card - Dwi Nurul lzzhati (JURNAL DIAN, 2011)
Human resources are the core of a system. The success of a company's success in improving the company's performance is highly dependent on the quality of human resources to get theMaximum Work System. lt also needs a measurement to maintain the performance achievement so it will enable to maintain and improve the efficiency and effectiveness of human resources.The approach of human resources Score Card, greatly assists the management in assessing performance against the appropriate level of interest in the company.Keywords: Human resources, performace, human Resources Score Card